Progress and Prospects of Bioelectrochemical Systems: Electron Transfer and Its Applications in the Microbial Metabolism - Zheng, Tianwen; Li, Jin; Ji, Yaliang; Zhang, Wenming; Fang, Yan; Xin, Fengxue; Dong, Weiliang; Wei, Ping; Ma, Jiangfeng; Jiang, Min (Frontiers in Bioengineering and Biotechnology, 2020)
Bioelectrochemical system which is a new prevailed bioengineering technology integrates microorganisms or enzymes with the electrochemical method to strengthen the reducing or oxidizing metabolism. Generally, the bioelectrochemical systems show the process referring to electrical power generation or achieving the reducing reaction with certain potential poised by means of electron transfer between the electron acceptor and electron donor. Researchers have focused on the selection and optimization of the electrode materials, design of electrochemical device, and screening of electrochemical active or inactive model microorganisms. Notably, all these means and studies are related to electron transfer: efflux and consumption. Thus, here we introduce the basic concepts of bioelectrochemical systems, and elaborate the extracellular and intracellular electron transfer, and the hypothetical electron transfer mechanism. Finally, intracellular energy generation and coenzyme metabolism along with electron transfer are summarized.